Leading a gifted and talented programme in an international school: an examination from a moral leadership perspective - Nemeth, Ferenc (2016)
This thesis presents an examination of leadership practice as it responds to the implementation of a gifted and talented program. The examination is conducted through the lens of moral leadership theories. This thesis heeds the call from researchers who have suggested the need for moral case studies to assist school leaders in 'making confident ethical judgments that transcend mere intuition' (Campbell, 1995: p. 605). Theories from moral philosophy and concepts from moral psychology are brought into the discussion in an attempt to address concerns with respects to the theoretical underpinnings of the concept moral leadership. The combined framework advances a model of a moral process that provides specific sign posts that allow for an inquiry into the moral decision making a school leader undergoes in addressing a moral issue. This study uses a multi-method research design involving both narrative and statistical analyses focused upon data generated from semi-structured interviews, questionnaires, observations, and document analysis. My analysis of key informants provides additional insight into the process that school leaders undergo in order to address a moral issue. The significance of the analysis was the generation of five categories: personal integrity, professional ethics, structural collaboration, exogenous influences and constructive concerns. Each of the five categories highlighted were influential in the decision to implement the gifted and talented program. The organisational and geographic context for this examination is an International School located in Turkey (IST).